xDSL technology for communications. - Huari E., Félix (2001)
Today the method more used to be connected to Internet consists in using a modem(individually), but due to the analogical nature of the phone lines, the modems cannot be connected to speeds of a LAN that reach 10-100 Mbps. Depending on necessities level, we can choose one of the connection types known as xDSL and it can be IDSL, ADSL, VSDL, HDSL, SDSL, etc., they are a group of technologies that provide a great with band allowing the symmetrical so much flow of information as asymmetric hich-speed.